Dicationic phenyl-2, 2′-bichalcophenes and analogues as antiprotozoal agents - Ismail, Mohamed A. (2010)
A series of phenyl-2, 2′-bichalcophene diamidines 1a-h were synthesized from the corresponding dinitriles either via a direct reaction with LiN(TMS)(2), followed by deprotection with ethanolic HCl or through the bis-O-acetoxyamidoxime followed by hydrogenation in acetic acid and EtOH over Pd-C. These diamidines show a wide range of DNA affinities as judged from their ΔTm values which are remarkably sensitive to replacement of a furan unit with a thiophene one. These differences are explained in terms of the effect of subtle changes in geometry of the diamidines on binding efficacy. Five of the eight compounds were highly active (below 6 nM IC(50)) in vitro against Trypanosoma brucei rhodesiense (T. b. r.) and four gave IC(50)values less than 7 nM against Plasmodium falciparum (P. f.). Only one of the compounds was as effective as reference compounds in the T. b. r. mouse model for the acute phase of African trypanosomiasis.